(untitled) (Foro de Educacion, 2022)
Students’ school experiences agglutinate and shape the influences of their social, cultural and school contexts. These experiences are dynamic, relational, and multidimensional and are configured in dialectical contexts of change and reproduction. In the school environment, central phenomena such as socialization and adaptation, social order, meritocracy, social inequalities are articulated, and students’ experiences are a fundamental construct to help deepen our understanding of these phenomena. To study school experiences, we designed a questionnaire (CEES) that collects students’ perceptions about the functions of the school system. The CEES was given to a sample of 848 secondary school students in Tenerife (the Canary Islands). Specifically, the factorial analysis yielded five key dimensions: school adaptation; the culture of effort; ideal model for students, ideal model for teachers and exclusion among peers. The relevance of these dimensions is that they allow us to identify the meanings of the school system based on students’ voices: consequently, their legitimacy is proven. Additionally, they can measure the aspects that determine students’ levels of identification with their school and to recognize the causes of school disaffection and problems related to academic performance.